2024
DOI: 10.3389/fpls.2024.1343593
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the adaptation of Japanese plum-type cultivars to reduced winter chilling in two regions of Spain

Brenda I. Guerrero,
Erica Fadón,
M. Engracia Guerra
et al.

Abstract: Japanese plum, like other temperate fruit tree species, has cultivar-specific temperature requirements during dormancy for proper flowering. Knowing the temperature requirements of this species is of increasing interest due to the great genetic variability that exists among the available Japanese plum-type cultivars, since most of them are interspecific hybrids. The reduction of winter chilling caused by climate change is threatening their cultivation in many regions. In this work, the adaptation perspectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…The other groups showed intermediate heat requirements. Our results showed some similarities with previous investigations reported by Ruiz et al, (2018) and Guerrero et al, (2024), which have showed that accumulated heat requirements for plum cultivars grown in Spain were 7,609 GDH and 6,934 on average, respectively. Besides, the cultivar Santa Rosa showed the earliest owering and the cultivar Singlobe showed the latest owering.…”
Section: Determination Of Chill and Heat Requirementssupporting
confidence: 91%
See 1 more Smart Citation
“…The other groups showed intermediate heat requirements. Our results showed some similarities with previous investigations reported by Ruiz et al, (2018) and Guerrero et al, (2024), which have showed that accumulated heat requirements for plum cultivars grown in Spain were 7,609 GDH and 6,934 on average, respectively. Besides, the cultivar Santa Rosa showed the earliest owering and the cultivar Singlobe showed the latest owering.…”
Section: Determination Of Chill and Heat Requirementssupporting
confidence: 91%
“…in Spain,Alburquerque et al, (2008) in the USA,Campoy et al, (2012) in South Africa andGuerrero et al, (2024) in Spain, recording low chilling accumulation during November and high accumulation from December to mid-February. The heat accumulation, estimated in GDH, between February and May during the two years of the experiment 2020-2021 and 2021-2022 were 15,000 and 13,800 GDH, respectively which showed increased heat availability from March.…”
mentioning
confidence: 98%